Analyzing the Impact of Human Resource Policies on Employee Satisfaction in Indian General Insurance Companies - Jaiswar, Sandeep Hiramani; Ingole, Mahendra (Journal of Neonatal Surgery, 2025)
Employee satisfaction plays a crucial role in the success of any organization, particularly in service-based industries like general insurance. This study examines the impact of human resource (HR) policies on employee satisfaction in Indian general insurance companies. The research aims to analyse employee perceptions of HR policies, evaluate their effectiveness in enhancing job satisfaction, and identify areas for improvement. A structured questionnaire was used to collect data from 100 employees across different job roles and experience levels. The study explores key aspects such as HR policy awareness, work-life balance, performance recognition, career growth opportunities, and overall job satisfaction. Findings reveal that while some employees view HR policies positively, a significant portion expresses dissatisfaction due to issues related to policy transparency, career progression, and work-life balance. Additionally, 53% of respondents suggest changes in HR policies to improve employee engagement and job satisfaction. The study highlights the need for better communication of HR policies, improved performance recognition programs, and enhanced career development initiatives. It also suggests implementing flexible work arrangements and strengthening employee feedback mechanisms to create a more positive work environment. The research concludes that while HR policies influence employee satisfaction, their effectiveness depends on proper implementation, transparency, and alignment with workforce expectations. Future studies can focus on longitudinal research, technological advancements in HR, and cross-sector comparisons to further understand the evolving role of HR policies in employee satisfaction. The insights from this study can help insurance companies enhance their HR strategies, leading to higher employee retention, engagement, and overall organizational success.